Rekonstruksi pemulihan kinerja pemasaran berbasis pemberdayaan pada pelaku usaha mikro kecil di Indonesia - Febrianur Ibnu Fitroh Sukono Putra; Risanda Alirastra Budiantoro; Awanis Linati Haziroh (Universitas Kristen Maranatha, 2021)
The Covid-19 pandemic has made most economic sectors, especially micro and small enterprises, stagnant and even bankrupt. This situation is what makes micro and small business enterprises change their sales strategy through digitalization schemes. The Covid-19 pandemic has indirectly prompted new changes in Indonesia's business style. Social media and marketplaces can become a new concept to make it easier for micro and small business actors to get more comprehensive marketing access. This study aims to initiate an ideal digital marketing adoption model for micro and small enterprise to restore economic conditions to their original state. The research method is an exploratory qualitative approach using primary data obtained from observations and interviews. The sampling technique used purposive sampling with the criteria of the sources being micro and small business actors assisted by the Department of Cooperatives and SMEs of Semarang, Surakarta, Grobogan, Pemalang, Purworejo. The flow of research analysis is data collection, data reduction, data presentation, and concluding. The results of this study indicate two alternative solution models, including (1) training and startup development; (2) training and scaleup development. The urgency of this research allows the government to carry out single submission online program management to minimize errors and monitor program progress. This solution model is expected to be a role model based on ta'awun (mutual relations) for other provincial governments in empowering micro and small business actors to become more optimal based on appropriate technology.